Innovation and Improvement in Instruction. Monograph Series No. 4 - Memphis State Univ., TN. J. W. Brister Library; Mayo, G. Douglas; Memphis State Univ., TN. J. W. Brister Library ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
The nine reports contained in this monograph describe in some detail projects to improve instruction initiated in 1974 at Memphis State University. The initial pages describe the criteria used to select the programs for funding. The nine projects fall into five areas: 1) computer-based instruction; 2) video technology; 3) individualized instruction and competency-based instruction; 4) development of instructional modules; and 5) simulation and gaming. (EMH)
ERIC Note: Some appendixes may not be reproducible due to marginal legibility of original document.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audiovisual Aids; Case Studies; College Instruction; Competency Based Education; Computer Assisted Instruction; Educational Games; Educational Innovation; Educational Television; Higher Education; Individualized Instruction; Instructional Improvement; Learning Modules; Material Development; Simulation; Memphis State University TN; Books